Trends in online radio as a way of supporting the construction of strategies tailored for the medium (2019)
By means of a literature review, this paper presents an analysis of trends that impact the radio at digital level to facilitate the strategic formulation of online stations from the identification of trends, the transformation of the medium and the recognition of digital actions. The methodological proposal was developed with the Micmac matrix in which three categories are considered: 1) characteristics of the radio as a means of diffusion, 2) digital consumption strategies, and 3) the relationship between audience and medium. This approach facilitates the process of gathering trends and information for its implementation. Secondary sources such as IAB, Hubspot, and P & M Magazine, among others, were used, taking the 306Radio digital station as a reference. As a result of using the aforementioned matrix, three trends that impact the radio at digital level were found. First, programmatic audio; secondly, programming mix; and thirdly, radio branded content. These trends, explored in a real context, facilitate the strategic approach through the support of new technologies for the medium.